Stress levels and coping strategy of nursing students in online learning during COVID-19 Pandemic. A mixed- methods study - Hemme Tambunan, Evelyn; Renolita Sinaga, Rosnancy (Investigación y Educación en Enfermería, 2023)
Objective. To explain the stress level and coping strategies of nursing students in online learning during Covid-19 pandemic. Methods. Explanatory sequential mixed method QUAN-QUAL study conducted at a private university in Bandung, Indonesia. Of the 260 nursing students, 157 consented to participate and answered a Depression Anxiety Scale- 42 (DDAS-42) and The Ways of Coping in the Indonesian version. The participants of the quantitative phase with the indicative of stress were interviewed individually (n=17) to provide an in-depth understanding of the students’ experiences of stress and coping strategy in online learning. Results. Almost one out of two students (47.1%) had some level of stress (16% between severe and extremely severe). Most nursing students (45.9%) used emotion focused coping strategies. Stress level was significantly higher among female students and internship academic level (%0.05). Nursing students’ sources of stress were new experiences and hindrances to online learning. Coping strategies included seeking support and positive acceptance. Conclusion. A high proportion of nursing students experienced stress during their education process in COVID-19 times; they used specially emotion-focused coping strategies to reduce barriers to online learning.